Police Discrimination, Misconduct, and Stigmatization of Female Sex Workers in Kenya: Associations with Delayed and Avoided Health Care Utilization and Lower Consistent Condom Use - David Kuria Mbote; Laura Nyblade; Caroline Kemunto; Kayla Giger; Joshua Kimani; Pia Mingkwan; Stella Njuguna; Emmanuel Oga; John D. Kraemer (Harvard FXB Center for Health and Human Rights, 2020)
Discrimination and violence against sex workers by police are common in many populations and are associated with negative health outcomes, as well as being per se violations of human rights laws and norms. There is a close and mutually reinforcing nexus between legally actionable rights violations and stigma, and reducing human rights violations against sex workers likely requires both legal and societal interventions that address both. In this paper, we first aim to estimate levels of discrimination, violence, and stigma against women sex workers by police in Kenya. Second, we aim to estimate the association between manifestations of discrimination and stigma, on the one hand, and general health care utilization and consistent condom use, on the other. Using data from a survey of Kenyan sex workers, we document widespread discrimination and stigma. Through regression analyses, participants with the highest levels of all three categories of manifestations of discrimination and stigma reported significant lower consistent condom use. Those with the highest levels of witnessed/heard manifestations were significantly more likely to delay or avoid needed health care, and the highest level of experienced manifestations were associated with a marginally significant increase in delay or avoidance. Our findings document a plethora of violations of human rights obligations under Kenyan and international law.